ENHANCING SPEAKING SKILLS IN HIGHER EDUCATION THROUGH CANVAS LMS: A STUDY IN BANDA ACEH - Firdaus; Yunisrina Qismullah Yusuf; Iskandar Abdul Samad; Hilda Delavari (English Review: Journal of English Education, 2025)
This study examines the effectiveness of Canvas, a web-based Learning Management System (LMS), in enhancing the speaking proficiency of first-semester students majoring in Psychology at Universitas Muhammadiyah Aceh, Indonesia. A quasi-experimental design was employed, with 30 students divided into 15 in the experimental group (Canvas) and 15 in the control group (Zoom). Both groups participated in five online learning sessions, with the first serving as a pre-test (offline), the next three as treatment sessions (online), and the final meeting as a post-test (offline). Students' speaking skills were assessed based on Vocabulary, Pronunciation, Grammar, Fluency, and Content aspects. Statistical analysis using paired sample t-tests in SPSS 26 confirmed significant improvements in all five speaking aspects for both groups, though the Canvas group outperformed the Zoom group across all measures. The results indicated that Canvas facilitated better engagement, structured learning, and interactive communication tools, leading to higher mean scores in Vocabulary and Fluency. A post-study questionnaire also revealed strongly positive student perceptions regarding Canvas's effectiveness in task submission and online learning accessibility. These findings support the integration of Canvas LMS in higher education curricula and have practical implications for EFL educators, policymakers, and curriculum designers in optimizing digital learning strategies. The study stresses Canvas as a pedagogically effective platform for developing students' communicative competence in English.